Protecting Environment through Criminal Sanction Aggravation (Universitas Negeri Semarang, 2022)
This paper aims to explores the provision of aggravating criminal sanction that protects environment in environmental legislation. By focusing on the four laws as its primary data source, this study employed doctrinal legal research. The results showed that the weight accorded to criminal sanctions in environmental legislation, has varied. The PPLH Law provides for the amplification of criminal threats directed at corporations by adding 1/3 (one-third) of the criminal sentence. Only companies are subject to the penalty aggravation provisions of the Mining Law, and they are only imposed with one-third of the maximum criminal provision of fines. In the PPPH Law, the imposition of criminal threats weight is simply related to the quantity component. If the culprit is a corporation or official, the criminal sanction aggravation is increased by one-third. In Plantation Law, if the offender is a corporate or a government official, then the criminal punishment is intensified. The environment is protected through acts prohibited by environmental legislation, but the criminal threat weight is not directed toward environmental preservation. Existing penalty aggravations are confined to only two types of criminal penalties: jail and fines, both of which have no direct connection to environmental protection. As a result, weighting criminal sanctions refers to the changing quality and quantity issues in order to safeguard the environment. The transition from criminal sanction to treatment, or from one type of treatment to another, was the focus of quality considerations, while the twofold criminal fine system was the focus of quantity element.